The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1984
DOI: 10.1177/104345428400100304
|View full text |Cite
|
Sign up to set email alerts
|

Donor-Patient Relationship in Pediatric Bone Marrow Transplantation

Abstract: Bone marra) transplantation is a reZatively new and aggressive procedure used i n t h e treatment o f leukemia, a p t a s t i c anemia, and severe i m n o d e f i c i e n t diseases. This paper addresses s p e c i f i c a l l y t h e psychological impact of the procedure on t h e r e t a t i o n s h i p betueen the donor and the recipient. The donor-patient relationship i s viewed i n the context of the family system, o i t h particular emphasis on t h e sibting retationships. Cases are presented t o demonstra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
27
0

Year Published

1987
1987
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 6 publications
1
27
0
Order By: Relevance
“…Siblings play a crucial role in identity development, by way of personal exchanges through which they define one another (Bank & Kahn, 1982). Research also highlights the importance of the sibling bond (Packman et al, 1997b;Wiley et al, 1984). The pediatric bone marrow transplantation (BMT) literature has shown that the sibling bond between the patient and sibling donor actually intensifies following BMT (MacLeod et al, 2003;Packman et al, 1997b;Wiley et al, 1984) where one sibling's provision of a life-saving measure for a brother or sister connects them in a unique way.…”
Section: Uniqueness Of Sibling Relationshipsmentioning
confidence: 97%
“…Siblings play a crucial role in identity development, by way of personal exchanges through which they define one another (Bank & Kahn, 1982). Research also highlights the importance of the sibling bond (Packman et al, 1997b;Wiley et al, 1984). The pediatric bone marrow transplantation (BMT) literature has shown that the sibling bond between the patient and sibling donor actually intensifies following BMT (MacLeod et al, 2003;Packman et al, 1997b;Wiley et al, 1984) where one sibling's provision of a life-saving measure for a brother or sister connects them in a unique way.…”
Section: Uniqueness Of Sibling Relationshipsmentioning
confidence: 97%
“…The donor selection procedure establishes a new relationship between the siblings and affects the entire family system (Wiley et al, 1984). At the time of tissue typing, siblings may compete for the role of donor, causing nondonors to feel excluded.…”
Section: Review Of the Literaturementioning
confidence: 99%
“…22 Nondonor siblings experience ambivalent feelings of both disappointment and relief, and may express guilt about these feelings of relief. 21 Wiley et al 21 suggested that the relationship between donor and recipient can change towards increased intimacy between the two. Rappaport 23 noted that the success of the transplant depends, in part, on the histocompatibility of donor and recipient; thus, the donor often perceives failure of engraftment as a case of 'my marrow wasn't good enough.'…”
Section: Studies On Siblings Of Pediatric Bmt Patientsmentioning
confidence: 99%
“…21 The donor selection procedure was thought to establish a new relationship between the siblings and affect the entire family system. 21 At the time of tissue typing, siblings may compete for the role of donor, causing nondonors to feel excluded.…”
Section: Studies On Siblings Of Pediatric Bmt Patientsmentioning
confidence: 99%
See 1 more Smart Citation